Synthesis, crystal structure and properties of hepta(ammonium) penta(1H-imidazol-3-ium) paratungstate B tetrahydrate. Issue 13 (3rd July 2021) - Srinivasan, Bikshandarkoil R.; Kundaikar, Savita A.; Morajkar, Sudesh M.; Näther, Christian; Bensch, Wolfgang
Abstract: An attempted isolation of the elusive diammonium tetraoxidotungstate (NH4 )2 [WO4 ] as its imidazole (Im) adduct resulted in the serendipitous formation of hepta(ammonium) penta(1H-imidazol-3-ium) paratungstate B tetrahydrate having formula [NH4 ]7 [ImH]5 [W12 O42 ]·4H2 O (1 ). The synthesis, vibrational spectra, crystal structure and thermal study of the mixed cationic paratungstate tetrahydrate 1 are reported. The structure of 1 consists of a centrosymmetric paratungstate [W12 O42 ] 12– anion devoid of internal hydrogen atoms, which is charge balanced by ammonium and 1H-imidazol-3-ium cations. One of the four unique NH4 + cations and one of the three crystallographically independent 1H-imidazol-3-ium cations are disordered around a center of inversion. The cations, [W12 O42 ] 12– anion and the unique lattice water molecules are joined with the aid of five varieties of hydrogen bonding interactions. A comparative study of twenty-three partaungstates is described. Thermal decomposition of 1 results in the formation of monoclinic tungsten trioxide WO3 . Abstract : UF0001